Advisory Unit 0510.0: The International Role of Educational Inspection - Álvarez Marín, Aránzazu; Quiroga Fernández, Francisco José (Avances en Supervisión Educativa, 2026)
This article examines the growing international profile of the Spanish Education Inspectorate within the framework of the State’s international education initiatives, focusing on its evolution towards strategic roles linked to advisory services. This work brings together two complementary lines of research: on the one hand, it incorporates the presentation held by Inspector Aránzazu Álvarez Marín at the ADIDE Madrid Conference (November 2025) on the international reach of educational inspection following the inclusion, for the first time, of education inspectors in the Technical Advisory Bodies, 0510, of the Foreign Education Programme; and, on the other hand, together with Inspector Francisco José Quiroga Fernández, it presents an academic reflection that broadens this scope, incorporating a semantic, regulatory, competency-based and empirical analysis of the system of access via open merit-based competition for the provision of posts for technical advisers abroad. The study examines the evolution of the calls for applications published by the Ministry of Education, Vocational Training and Sport, the stages of the procedure, as well as the competency profile required to perform these functions in international educational contexts, emphasising the technical and competency-based aspects of the inspector’s role and drawing a comparison with the final report of the Proposal for the Framework of Professional Teaching Competencies.